Antiproliferation potential of Botto-botto (Chromolaena odorata L.) leaves methanol extract fraction against HeLa Cell Line - Muhammad Rusdi; Haeria Haeria; Nursalam Hamzah; Afrisusnawati Rauf; Faradibha Amriani (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
Botto-botto (Chromolaena odorata L.) was one of plants that its leaves used empirically in South Sulawesi society as wound and anti-inflammatory drugs. This study aimed to determine the potential of Botto-botto toward cancer cells (HeLa Cells) and normal cells (Vero cells) using the MTT assay method (Microculture Tetrazolium Salt Method). Ethyl acetate extract from methanol extract being fractionated by vacuum liquid chromatography method by a different polarity level of solvent. Cytotoxic effect test was using MTT method to cancer cells (HeLa), and normal cells (Vero) with the percent parameter of cell growth inhibition. Selectivity index was determined from percentage of cancer cell growth inhibition ratio of cancer cells to normal cells. The results showed that A, B, C, D, E, F, and G fractions had a selectivity index on HeLa cells at 0.845, 3.387, 2.004, 1.508, 1.625, 1.284, 1.299. This result proved that B fraction of methanol extract of Botto-botto leaves had a potential to be developed as chemotherapy agents in increasing the effectiveness treatment of cervix cancer.